The Sense of Self Over Time: Assessing Diachronicity in Dissociative Identity Disorder, Psychosis and Healthy Comparison Groups - Dorahy, Martin J.; Huntjens, Rafaële J. C.; Marsh, Rosemary J.; Johnson, Brooke; Fox, Kate; Middleton, Warwick (Frontiers in Psychology, 2021)
Dissociative experiences have been associated with diachronic disunity. Yet, this work is in its infancy. Dissociative identity disorder (DID) is characterized by different identity states reporting their own relatively continuous sense of self. The degree to which patients in dissociative identity states experience diachronic unity (i.e., sense of self over time) has not been empirically explored. This study examined the degree to which patients in dissociative identity states experienced diachronic unity. Participants were DID adults (n = 14) assessed in adult and child identity states, adults with a psychotic illness (n = 19), adults from the general population (n = 55), children from the general population (n = 26) and adults imagining themselves as children (n = 23). They completed the Diachronic Disunity Scale, the Dissociative Experiences Scale, and the Self-Concept Clarity Scale. Diachronic disunity was not limited to psychiatric groups, but evident to some degree in all adult and child samples. The DID adult sample experienced more dissociation and self-confusion than the psychosis and adult comparison groups, but did not differ on the diachronic measure. DID patients in their child identity states and child comparisons showed disunity and were significantly different from child simulators, who showed relatively more unity. Results suggest that DID patients in either adult or child dissociative identity states, like those in other samples, do not universally experience themselves as having a consistent sense of self over time.